2014
DOI: 10.1007/s11010-014-2200-6
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ANLN by lentivirus inhibits cell growth and migration in human breast cancer

Abstract: Anillin (ANLN), an actin-binding protein, is required for cytokinesis. Recently, ANLN has been identified as a biomarker in diverse human cancers; however, the precise role of ANLN in breast cancer remains unclear. In this study, we firstly detected the expression of ANLN in 71 patients with breast cancer by immunohistochemistry, and found ANLN was highly expressed in breast cancer tissues. To evaluate the function of ANLN in breast cancer cells, we employed lentivirus-mediated RNA interference to knock down A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 26 publications
6
72
0
Order By: Relevance
“…Similar to the recently published findings by Zhou et al [14], we found that transient knockdown of ANLN protein expression in breast cancer cell lines resulted in a significant accumulation of cells in the G2/M phase of the cell cycle. Although experiments performed on only two different cell lines with differences in ER expression do not allow for general conclusions, we found that the impact of ANLN on these two breast cancer cells were similar, independent of ER status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the recently published findings by Zhou et al [14], we found that transient knockdown of ANLN protein expression in breast cancer cell lines resulted in a significant accumulation of cells in the G2/M phase of the cell cycle. Although experiments performed on only two different cell lines with differences in ER expression do not allow for general conclusions, we found that the impact of ANLN on these two breast cancer cells were similar, independent of ER status.…”
Section: Discussionsupporting
confidence: 92%
“…Using multivariable cox regression analysis, ANLN was suggested as an independent prognostic factor for BCSS following adjustment for tumor size, nodal status, tumor grade, hormone receptor status, HER2 status, Ki-67, tumor type, age and the proteins PDZ-Domain Containing 1 (PDZK1) and PDZ-Binding Kinase (PBK). In a recent study based on a cohort consisting of 71 patients diagnosed with primary breast cancer, the rate of ANLN expression was shown to be significantly higher in breast cancer compared to normal breast tissue [14]. In this study, ANLN knockdown was also shown to inhibit cell migration, colony formation and cell cycle progression.…”
Section: Introductionmentioning
confidence: 53%
“…23 and Zhou et al . 28 , who reported that ANLN participated in the proliferation and invasion of lung cancer and breast cancer, respectively. As we proved that ANLN-targeting siRNA was effective at inhibiting cancer cell growth and invasion, ANLN might become a candidate target for development of anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…NREP and P311) was decreased in nc886 KO (Figure 5). These genes have been reported to inhibit tumor cell proliferation and migration when suppressed [22, 23] and their lower expression was associated with good survival of patients in the TCGA cohort (Figure 5). Therefore, nc886 and some of its associated genes could be an informative marker in deciding the extent of surgery in preoperative settings and in determining the dose of radioactive iodine therapy after surgery to improve the patient's outcome.…”
Section: Discussionmentioning
confidence: 99%